Neural Signature of DCD: A Critical Review of MRI Neuroimaging Studies - Biotteau, Maëlle; Chaix, Yves; Blais, Mélody; Tallet, Jessica; Péran, Patrice; Albaret, Jean-Michel (Frontiers in Neurology, 2016)
The most common neurodevelopmental disorders (e.g., developmental dyslexia, autism, attention deficit hyperactivity disorder) have been the subject of numerous neuroimaging studies, leading to certain brain regions being identified as neural correlates of these conditions, referring to a neural signature of disorders. Developmental coordination disorder (DCD), however, remains one of the least understood and studied neurodevelopmental disorders. Given the acknowledged link between motor difficulties and brain features, it is surprising that so few research studies have systematically explored the brains of children with DCD. The aim of the present review was to ascertain whether it is currently possible to identify a neural signature for DCD, based on the 14 magnetic resonance imaging (MRI) neuroimaging studies that have been conducted in DCD to date. Our results indicate that several brain areas are unquestionably linked to DCD: cerebellum, basal ganglia, parietal lobe, parts of the frontal lobe (medial orbitofrontal cortex and dorsolateral prefrontal cortex). However, research has been too sparse and studies have suffered from several limitations that constitute a serious obstacle to really addressing the question of a well-established neural signature for DCD.